The Game Definition Game: A Review. (September 2017) - Stenros, Jaakko
In this article, over 60 definitions of games since the 1930s are reviewed in order to pinpoint what those definitions agree on and, more importantly, what they disagree on. This article is conceived of as a tool game scholars can use to better position themselves in regard to the concept of "game" by working out their answers to the 10 questions regarding game definition presented in here.